1984
DOI: 10.2527/jas1984.5951262x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Nτ-Methylhistidine Excretion and Muscle Protein Degradation in Growing Beef Steers

Abstract: The urinary excretion of N tau-methylhistidine (N tau-MH) was studied quantitatively in growing Hereford steers to measure muscle protein degradation (MPD) at different stages of growth. The amount of MPD and the fractional rate of protein breakdown (FBR) on 28, 42, 56 and 63 d of the experiment were calculated from the 24-h urinary N tau-MH excretion. The steers grew rapidly during the initial phase of the study; the growth rate was higher on d 56 (P less than .01) than on d 42 of the study. On d 63, there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
4
10
0
2
Order By: Relevance
“…In the present study, muscle mass was assumed to be 33% of body weight (Allen et al, 1968). Based on this value, the FBR we observed was similar to data reported by McCarthy et al (1983), 2.46 to 3.42%/d, but slightly higher than data reported by Gopinath and Kitts (1984), 2.07 to 2.84%/d. Results indicate that FBR was higher (P < .05) for RFC than for ALC after realimentation (Table 3).…”
Section: Results and Dlscusslonsupporting
confidence: 77%
See 3 more Smart Citations
“…In the present study, muscle mass was assumed to be 33% of body weight (Allen et al, 1968). Based on this value, the FBR we observed was similar to data reported by McCarthy et al (1983), 2.46 to 3.42%/d, but slightly higher than data reported by Gopinath and Kitts (1984), 2.07 to 2.84%/d. Results indicate that FBR was higher (P < .05) for RFC than for ALC after realimentation (Table 3).…”
Section: Results and Dlscusslonsupporting
confidence: 77%
“…Cattle with ad libitum access to feed had a higher (P < .05) urinary W-MH excretion during the first two collection periods; however, it was lower (P < .05) for ALC than for RFC at 118 d and not different at 146 d Fable 1). The quantities of W-MH excreted by our steers (Table 1) were in a range similar to that reported by McCarthy et al (1983) and Gopinath and Kitts (1984) but slightly higher than reported by Nishizawa et al (1979) and Harris and Milne (1981 Body weights of ALC were higher ( P c .05) than those of restricted-fed cattle at the last four sampling periods (Table 2). A linear (P c .05) increase in body weight of ALC with age was observed.…”
Section: Results and Dlscusslonsupporting
confidence: 75%
See 2 more Smart Citations
“…Values reported for fractional rates of muscle protein degradation have ranged from 26.5% per day in breast muscle of young chicks (Maruyama et al, 1978) to 3.4 to 4.4% per day in 22-to 45-kg male pigs (Mulvaney et al, 1985) to 2 to 3.3% per day in growing cattle (McCarthy et al, 1983;Gopinath and Kitts, 1984). Table I shows that if the rate of muscle protein degradation in a 454-kg steer were decreased by only 10% from 3.0% to 2.7% per day, the rate of live weight gain in this animal would more than double from 1.20 to 2.55 kg/day.…”
Section: Chaptermentioning
confidence: 99%